Properties of nanomodified concrete in dry hot external conditions - Shyshkin А.; Shyshkina А. (Ways to Improve Construction Efficiency, 2020)
Based on the analysis of literary sources, the article determines the possibility of producing fine-grained concrete for monolithic concreting with water modified with structured colloidal surfactants. Peculiarities of monolithic concreting in dry hot conditions are given and the issues of preparation technology of fine-grained concrete based on cement systems with nanomodified structured colloidal surfactants water are considered. It combines knowledge of the laws of structure formation and modification of the systems “Portland cement - micro-fillers - superplasticizer - colloidal surfactants” to ensure the technological and operational properties of concrete in the face of changing factors of its technology and operation. An increase in the rate of heating of concrete leads to a decrease in the strength of concrete. However, the decrease in strength of concrete structured by colloidal surfactants is much less than in concrete that does not contain these substances. The results of studies have established that the use of superplasticized systems based on cement and structured water allows directionally controlling technological properties and creating a solid concrete structure with improved construction and technical properties during hardening in dry, hot temperature conditions. The results of the studies allow us to draw the following conclusions: the introduction of colloidal hydrophobic surfactants into the composition of concrete in ultra-low concentrations leads to a decrease in the stratification of cellular concrete along the height of the product; the introduction of concrete to colloidal hydrophobic surfactants in ultra-low concentrations leads to a decrease in its thermal conductivity; the introduction of colloidal hydrophobic surfactants into the composition of concrete in ultra-low concentrations leads to an increase in its stability, both to the action of elevated temperatures and low (frost). This creates the possibility of early loading of structures, shortening the production cycle, increasing the turnover of formwork and accelerating the construction of monolithic buildings and structures in dry, hot temperature conditions.